2002
DOI: 10.1016/s0167-4889(02)00187-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of human organic anion transporter 4 in the transport of ochratoxin A

Abstract: The purpose of this study was to investigate the characteristics of ochratoxin A (OTA) transport by multispecific human organic anion transporter 4 (hOAT4) using mouse proximal tubule cells stably transfected with hOAT4 (S(2) hOAT4). Immunohistochemical analysis revealed that hOAT4 protein was localized to the apical side of the proximal tubule. S(2) hOAT4 expressed hOAT4 protein in the apical side as well as basolateral side and the cells were cultured on the plastic dish for experiments. S(2) hOAT4 exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 31 publications
3
90
0
4
Order By: Relevance
“…These findings contrasted with that of the renal basolateral tertiary active transport system, suggesting that OAT4 may be localized to the apical membrane in renal tubules. Apical expression of OAT4 was then confirmed in renal proximal tubules [73]. Further assessment of OAT4 revealed that it was able to be transstimulated by dicarboxylates [74].…”
Section: Oat4 (Slc22a11)mentioning
confidence: 87%
“…These findings contrasted with that of the renal basolateral tertiary active transport system, suggesting that OAT4 may be localized to the apical membrane in renal tubules. Apical expression of OAT4 was then confirmed in renal proximal tubules [73]. Further assessment of OAT4 revealed that it was able to be transstimulated by dicarboxylates [74].…”
Section: Oat4 (Slc22a11)mentioning
confidence: 87%
“…These clones exhibited 63% identity in their amino acid sequences. mOATLP1 exhibited amino acid homology from 37% to 63% (Lopez-Nieto et al, 1997;Brady et al, 1999;Kobayashi et al, 2002;Monte et al, 2004;Youngblood et al, 2004). Human OAT4 also exhibited high homology to mOATLP1 (51%).…”
Section: Discussionmentioning
confidence: 99%
“…The OAT1 and OAT3 proteins are known to be localized to the basolateral membrane, and OAT2 and OAT4 are known to be localized in the apical membrane of nephrons (Hosoyamada et al, 1999;Cha et al, 2001;Babu et al, 2002;Kojima et al, 2002). Our results showed that the mOAT5 protein was localized in the apical membrane of the late proximal tubule.…”
Section: Discussionmentioning
confidence: 99%
“…The OAT1 and OAT3 proteins are localized to the basolateral membrane, and OAT2 and OAT4 in the apical membrane of nephrons (Hosoyamada et al, 1999;Cha et al, 2001;Babu et al, 2002;Kojima et al, 2002). OCT1 and OCT2 proteins are localized in the basolateral membrane of renal tubules.…”
Section: Discussionmentioning
confidence: 99%